SKRINING FITOKIMIA BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) SEBAGAI OBAT BISUL - Putu Lakustini Cahyaningrum; Putu Lasmi Yuliyanthi Sapanca; I Gusti Ayu Diah Yuniti; Cokorda Javandira (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2023)
Dayak onions (Eleutherine sp.) are plants that are often found in the Kalimantan region. Dayak onion tubers are plants that contain flavonoid compounds so they have the potential to be developed and used as traditional medicine by the community. The chemical compounds contained in Dayak onions include 15 compounds including flavonoid and naphthaquinone derivatives. Several studies show the extract's activity as anti-inflammatory, antidiabetic, anticancer, antidiabetic, antimicrobial. This research aims to find out about the Dayak onion plant which is still very lacking, especially in its development as a raw material for the development of biopharmaceuticals. Until now, the development and use of this plant is very minimal, even though the benefits of this plant have long been felt by local rural communities